2014
DOI: 10.1177/0886260514539759
|View full text |Cite
|
Sign up to set email alerts
|

A Cycle of Violence? Examining Family-of-Origin Violence, Attitudes, and Intimate Partner Violence Perpetration

Abstract: Exposure to violence in the family-of-origin has consistently been linked to intimate partner violence (IPV) perpetration in adulthood. However, whether the transmission of violence across generations is role- and gender-specific still remains unclear. The current study examined the effects of experiencing child abuse and observing parental violence on IPV perpetration among a sample of male arrestees (N = 303). The differential effects of observing violence perpetrated by same-sex (father to mother), opposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
81
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 46 publications
(58 reference statements)
8
81
0
9
Order By: Relevance
“…Further, studies have shown a relationship between childhood exposure to IPV in the household and experience of physical violence as discipline in childhood with male perpetration and female experience of IPV in adulthood. Yet, not all children exposed to IPV in childhood will use violence in their adult relationships (Eriksson & Mazerolle, 2015; Hotaling & Sugarman, 1986). In rural, post-conflict DRC male and female participants described IPV as a concern for their child’s future development including their future use of violence, therefore, interventions should consider addressing the family, including prioritizing child development, as an opportunity to prevent and respond to IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Further, studies have shown a relationship between childhood exposure to IPV in the household and experience of physical violence as discipline in childhood with male perpetration and female experience of IPV in adulthood. Yet, not all children exposed to IPV in childhood will use violence in their adult relationships (Eriksson & Mazerolle, 2015; Hotaling & Sugarman, 1986). In rural, post-conflict DRC male and female participants described IPV as a concern for their child’s future development including their future use of violence, therefore, interventions should consider addressing the family, including prioritizing child development, as an opportunity to prevent and respond to IPV.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Eriksson and Mazerolle (2015) on child abuse, which observed IPV by male perpetrators, indicates how the influence of the environment can explain the transmission of violence across groups and generations through children learning from the family and the society at large. The results of the study indicate that violence is also transmitted through the acquisition of beliefs, norms and attitudes that individuals conform to that are considered as appropriate behaviour in society (Eriksson & Mazerolle, 2015). This speaks to the internalisation of social norms that condone the abuse of women, which in turn reinforces the acceptability of IPV against women.…”
Section: Theoretical Underpinningsmentioning
confidence: 89%
“…8 Witnessing IPV can also affect the attitudes and behaviors of children, increasing the likelihood that they will either perpetrate or experience IPV as adults. 9 Further complicating the issue is the bidirectional association between IPV and mental health. Depression has been linked to IPV both as a consequence of experiencing such behavior and as a risk factor.…”
mentioning
confidence: 99%